Autonomous Region in Muslim Mindanao – Bangsamoro Republic - Daria Panarina; Kirill Petrov (Международная аналитика, 2019)
Since XV-th century, when first Muslim state has been formed at Mindanao island in the south of the Philippines, practically two very different societies had to co-exist on the territory of the country: Muslims and Filipinos. It created a problem ad numerous conflicts which have not been solved so far. The aggravation between the Filipinos and the inhabitants of the southern island of Mindanao, which occurred in the XX-th century, led to a series of peace negotiations and attempts to reach political consensus. The idea of creating an autonomous territory in Mindanao within the framework of the Republic of the Philippines was framed in the form of a law, repeatedly elaborated, implemented, but without much success. Over the past 22 years, disagreements and a threat to the security of the region preserved, and strong tensions remained between the government of the Philippines and the Islamic leaders of Mindanao. When President Duterte came to power, another attempt was made to resolve this conflict, and for the first time in many years, a law was ratified based on the results of the plebiscite. This law can become the basis for the successful implementation of the idea of autonomy of Mindanao. However, it should be noted that in the near future the likelihood of armed clashes, provocations and serious terrorist acts by the forces of extremist groups in Mindanao is quite high.